Women in Christianity in the Modern Age
1 online resource.
Keywords: "Women in Christianity in the Modern Age examines the role of women in Christianity in the 20th and early 21st Centuries. This edited volume includes eight important contributions from academics in the field. The modern era has been an age of social and religious upheaval, and the ravages of global warfare and changes to women's role in society have made the examination of the place of women in religion a key question in theology. From theological concerns - engagements with the biblical texts by feminist and anti-feminist theologians, the modern role of Mary and women saints - to political and social debates on women's ministry and place in society, and cultural shifts as expressed through theologically inspired artwork by women, Women in Christianity in the Modern Age provides an overview and in-depth studies of a tumultuous and changing era. This insightful text will be of key interest to students and scholars in Religion and Cultural Studies"--